Melancholia of freedom : social life in an Indian township in South Africa - Hansen, Thomas Blom, 1958- (ACLS Humanities E-Book., 2012)
The end of apartheid in 1994 signaled a moment of freedom and a promise of a nonracial future. With this promise came an injunction: define yourself as you truly are, as an individual, and as a community. Almost two decades later it is clear that it was less the prospect of that future than the habits and horizons of anxious life in racially defined enclaves that determined postapartheid freedom. In this book, Thomas Blom Hansen offers an in-depth analysis of the uncertainties, dreams, and anxieties that have accompanied postapartheid freedoms in Chatsworth, a formerly Indian township in Du.